Brandeis modern Hebrew : intermediate to advanced - Ringvald, Vardit; Porath, Bonit; Peleg, Yaron; Shorr, Esther (Brandeis University Press, 2013)
"Written by the core faculty of the Hebrew program at Brandeis University, the pilot edition of Brandeis Modern Hebrew, Intermediate to Advanced serves as a sequel to the well-known volume for beginners. It contains the functional and contextual elements to bring users' Hebrew language proficiency to the intermediate level and introduce students to skills they need to become advanced in their use of the language. This volume reflects key principles of the Brandeis University Hebrew curriculum. These include: Placing emphasis on the learner's ability to use Hebrew in four skill areas: listening, reading, speaking, and writing; Contextualizing each unit within a specific subject or theme; Exposing the student to authentic materials and exploring aspects of Israeli and Jewish culture through language drills and reading passages"--